Buns & Dou / Izazi Naqiyah Zol Arduan - Zol Arduan, Izazi Naqiyah (2021)
Buns & Dou. is a bakery that more focus on buns because everyone does eat buns whenever they want and needs. As we know, buns are a common food we hear about, and everyone love to have it because buns are a very suitable food for everyone. So, in Buns & Dou. we prepare a variety of buns to fulfil customer’s needs. Other than that, Buns & Dou. is trademark for our business. The reasons we choose “Buns & Dou” is because it symbolizes the combination between dough and buns or to be more specific it shows that the buns is made of dough and these two are very interesting combination. Our bakery is located at Shah Alam, Selangor with very strategy location where it easy for people to get our buns. Moreover, the main objective of this business is we want to offer the best buns to customer with affordable price and the best quality. We want them to taste the fantastic of our buns and they will remember the taste of this buns. Our buns are more likely to be known as “fluffy buffy” due to the softness of the buns itself. Hence, our buns provide a good insight for the continuation of sale to our customers. Furthermore, we provide the excellent and friendly services to our customers so that they will put trust on us. We also believe that with offering the high quality service and excellent food the financial will be success to achieved.